Spirometry and respiratory disease risk factors in firefighters in Almaty - D. V. Vinnikov; Z. D. Tulekov; L. A. Strizhakov; S. A. Babanov; N. E. Lavrentyeva (Медицинский вестник Юга России, 2023)
Objective: to ascertain respiratory symptoms, lung function and selected respiratory disease risk factors in firefighters of the city of Almaty. Materials and methods: N=1379, 91% males, firefighters working in Almaty were recruited at the annual screening, where CAT (COPD Assessment Test) and mMRC (Modified Medical Research Council) questionnaires were offered to quantify the severity of respiratory symptoms. We also assessed respiratory risk factors, including cigarette smoking, exposure to environmental tobacco smoke, fossil fuel use for heating and cooking, and regular physical activity, followed by spirometry. Vital capacity (VC), forced VC (FVC) and forced expiratory volume in one second (FEV1) were measured. Results: Median age was 28 (interquartile range (IQR) 25-35) years, years in service median 5 (IQR 3-13) years. 41% of employees were daily cigarette smokers (significantly more among males, 43 vs. 16%), whereas 93% were exposed to environmental tobacco smoke and only 57% were engaged in regular leisure physical activity. With the overall low score of respiratory symptoms, the prevalence of postbronchodilator FEV1/FVC reduction below lower limit of normality in males was 2%, whereas the diagnosis of chronic bronchitis in the past was found in 2% of participants. Conclusions: healthy worker effect in firefighters of Almaty can explain very low prevalence of bronchoobstructive syndrome among those enrolled in this analysis, even despite high smoking prevalence.